Inhibition of Glycolysis Alleviates Chronic Unpredictable Mild Stress Induced Neuroinflammation and Depression-like Behavior - Bing Liu; Ke Dong; Xiaobing Chen; Huafeng Dong; Yun Zhao; Xue Wang; Zhaowei Sun; Fang Xie; Lingjia Qian (Brain Sciences)
Background: Growing evidence suggests that glucose metabolism plays a crucial role in activated immune cells, significantly contributing to the occurrence and development of neuroinflammation and depression-like behaviors. Chronic stress has been reported to induce microglia activation and disturbances in glucose metabolism in the hippocampus. Aims: This study aims to investigate how chronic stress-mediated glycolysis promotes neuroinflammation and to assess the therapeutic potential of the glycolysis inhibitor, 2-deoxy-D-glucose (2-DG), in a model of chronic stress-induced neuroinflammation and depression-like behavior. Methods: In in vitro studies, we first explored the effects of 2-DG on the inflammatory response of microglia cells. The results showed that corticosterone (Cort) induced reactive oxygen species (ROS) production, increased glycolysis, and promoted the release of inflammatory mediators. However, these effects were reversed by intervention with 2-DG. Subsequently, we examined changes in depression-like behavior and hippocampal glycolysis in mice during chronic stress. The results indicated that chronic stress led to prolonged escape latency in the Morris water maze, increased platform-crossing frequency, reduced sucrose preference index, and extended immobility time in the forced swim test, all of which are indicative of depression-like behavior in mice. Additionally, we found that the expression of the key glycolytic enzyme hexokinase 2 (HK2) was upregulated in the hippocampus of stressed mice, along with an increased release of inflammatory factors. Further in vivo experiments investigated the effects of 2-DG on glycolysis and pro-inflammatory mediator production, as well as the therapeutic effects of 2-DG on chronic stress-induced depression-like behavior in mice. The results showed that 2-DG alleviated chronic stress-induced depression-like behaviors, such as improving escape latency and platform-crossing frequency in the Morris water maze, and increasing the time spent in the center of the open field. Additionally, 2-DG intervention reduced the level of glycolysis in the hippocampus and decreased the release of pro-inflammatory mediators. Conclusions: These findings suggest that 2-DG can mitigate neuroinflammation and depressive behaviors by inhibiting glycolysis and inflammatory responses. Overall, our results highlight the potential of 2-DG as a therapeutic agent for alleviating chronic stress-induced neuroinflammation through the regulation of glycolysis.